Network pharmacology dissection of multiscale mechanisms for jiaoqi powder in treating ulcerative colitis. (15th July 2021) - Wen, Shuting; Zhong, Zhuotai; He, Long; Zhao, Dike; Chen, Xu; Mi, Hong; Liu, Fengbin
Abstract: Ethnopharmacological relevance: The incidence of ulcerative colitis (UC) is increasing worldwide, making it a serious public health challenge. Currently, there are no accepted curative treatments for UC. As such, the exploration of new therapeutic strategies for UC treatment is of considerable clinical importance. Jiaoqi powder (JQP) is a classic Chinese medicinal formula commonly used as a complementary and alternative medicine for treating gastrointestinal bleeding. JQP is thus a potential alternative medicine for UC treatment. However, the protective mechanism underlying the action of JQP has not been elucidated, thereby, necessitating further studies to decipher the mechanisms involved in the complex interplay among its components. Aim of the study: To explore the protective effect of JQP against UC and to further investigate its mechanism in silico and in vivo using a systems pharmacology approach. Materials and methods: A systems pharmacology approach was used to predict the active components of JQP. Putative targets and the potential mechanism of JQP on UC were obtained through target fishing, network construction, and enrichment analyses. An animal-based model of dextran sodium sulfate (DSS)-induced colitis in C57BL/6 mice was further used to validate the treatment mechanisms of JQP. The underlying pharmacological mechanisms of JQP in UC were determined using polymerase chain reaction tests, histological staining, immunohistochemistry, enzyme-linked immunoassays, and flow cytometry analysis. Results: In this study, 17 effective components and 941 potential targets of JQP were identified. Similarly, 2104 UC-related targets were also identified. Construction of PPI networks led to the identification of 184 putative therapeutic targets of JQP. Sixty-nine core targets among these 184 were further screened based on their DC values. Gene ontology (GO) functional and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses revealed that the core targets were primarily enriched in immune response and inflammatory signalling pathways. Subsequent animal-based in vivo experiments revealed that JQP ameliorated symptoms and histological changes in DSS colitis by significantly impairing DSS's ability to induce high expression levels of NF-κB/p65, IL-1β, IL-6, and TNF-α. JQP also reduced the levels of COX-2, CCL2, CXCL2, HIF-1α, MMP3 and MMP9 and regulated the Th17/Treg cell balance in DSS-induced mice. Conclusions: This study demonstrated that JQP could treat UC by improving the mucosal inflammatory response, repairing the intestinal barrier, and modulating the Th17/Treg immune balance. The results of this study provide new insights into UC treatment and further elucidate the theoretical and practical implications of the pharmaceutical development of TCMs. Graphical abstract: Image 1 Highlights: Integrate systems pharmacology and in vivo validation are used in efficacy studies. Demonstrate JQP can treat UC by regulating immune response and limiting inflammation. Provide novel perspectives on the development of therapeutic avenues in UC.